Optimization of bio-based cellulose-phosphate hydrogel production from rice husk waste using the Taguchi method - Aprilyanti, Selvia; Pratiwi, Irnanda; Andalia, Winny; Aprianti, Tine; Faritzie, Hariman Al (Teknomekanik, 2026)
This work reports the development and statistical optimization of a fully Bio-based absorbent hydrogel synthesized from rice husk–derived cellulose via phosphoric acid crosslinking. Cellulose was extracted through sequential chemical treatments and subsequently converted into a phosphate-crosslinked hydrogel using a controlled synthesis process. A Taguchi L16 (4⁵) orthogonal array was employed to optimize four key synthesis parameters: cellulose content, reaction time, heating temperature, and phosphoric acid volume. Hydrogel structure and morphology were characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). FTIR results confirmed the formation of phosphate ester linkages, indicating successful crosslinking, while SEM observations revealed a porous and interconnected network structure favorable for water absorption. The optimized hydrogel formulation achieved a maximum swelling ratio of 91.25 g/g, demonstrating effective absorbent performance despite the absence of synthetic monomers or grafting agents. These findings indicate that rice husk waste can be efficiently valorized into an environmentally benign absorbent material through a simple and statistically guided synthesis route, supporting sustainable hydrogel development and agricultural waste utilization.